A Software Process Gap Analysis Methodology for Very Small Entity - Kittitouch Suteeca (2020)
© 2020 IEEE. Nowadays, the demand for information technology and software are increasing. Many software development units are established. The most of units are very small entity (VSE.) which a software development unit include not over 25 people. They encounter many problems in their work. The software process improvement (SPI) is a methodology to reduce the problem. This paper focuses on to evaluate and analyze the processes of VSEs reference by ISO/IEC 29110 standard. The standard consists of two processes, which are Project management and Software implementation. The main objective of this research is to design a methodology for displaying the gap between the current process and standard. The result of the evaluation can lead to the VSE. prioritize the risk when they implement standard to the organization.